Lengyelország légi személyközlekedésének közelmúltbeli dinamikus növekedése, a lengyel légi "boom" legfrissebb trendjei - Pintér, Ákos (Közép-Európai Közlemények, 2012)
The Polish air traffic has been experiencing a dynamic development in recent years. The country’s air passenger traffic has grown 3.5 times more since the turn of the millennium and with more than 19 million passengers Poland ranks clearly the first among the post-socialist countries of Central and Eastern Europe. In the dynamic development of the 11 Polish airports, which serve domestic and international passenger air traffic, has many reasons. The prime reason for the increase in passenger traffic is the emergence of Low-Cost Carriers offering more favourable prizes, in the favour of regional airports. Guest workers from western Europe can reach Poland easier by air and North-American citizens of Polish decent arrive to visit relatives in their ’original homeland’. In the case of some cultural centres in the countryside tourism has intensified which also has a role in the dynamic increase of air traffic.